Procalcitonin as a Sepsis Marker in Patients of Critical Care Unit - Jasmine, Rezina; Giti, Susane; Khan, Arif Ahmed; Jubaida, Nishat; Naznin, Lubna (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Introduction: The aim of this study was to observe the diagnostic role of procalcitonin to evaluate sepsis and assess the level of inflammation for the patients of Critical Care Unit of different departments. Methods: This cross sectional, prospective and observational study was conducted at Armed Forces Institute of Pathology on the patients at Critical Care Unit of Paediatric, Surgery, Gynae and Medicine department in a tertiary care hospital (Combined Military Hospital, Dhaka) from June, 2020 to May, 2021. Total 106 patients were enrolled in this study. As the study was conducted during corona pandemic, RT-PCR test for Corona virus disease 2019 (COVID-19) along with serum procalcitonin and bacterial culture and sensitivity tests for different samples were prescribed for all 106 patients. Result: Out of 106 patients, 30.2% (32) patients were found positive and 69.69% (74) were found negative for COVID- 19 and 14.15% (15) patients had clinical documentation of bacterial co-infection, confirmed by blood, respiratory, or urine culture. After PCT test, 20.75 % (22) samples were found with severe sepsis or septic shock, 7.54% (08) samples were found with systemic infection, 18.06% (20) samples were with possible systemic infection, 31.13 % (33) samples were with local infections and 21.69% (23) were found within normal ranges of PCT. Conclusion: This study supports the importance of the diagnostic role of PCT to assess the level of sepsis as well as presence of co-infection which suggests that PCT level is a good biomarker for early diagnosis, assessment and treatment of patients in CCU. J Bangladesh Coll Phys Surg 2023; 41: 198-204